PRE‐ AND POSTNATAL MODIFICATIONS IN PARENTAL MENTAL REPRESENTATIONS IN THREE CASES OF FETAL GASTROSCHISIS DIAGNOSED DURING PREGNANCY. Issue 6 (10th November 2015) - Tripani, Antonella; Pellizzoni, Sandra; Giuliani, Rosella; Bembich, Stefano; Clarici, Andrea; Lonciari, Isabella; Ammaniti, Massimo
ABSTRACT: The aim of this study was to identify possible effects of gastroschisis on parents' intrapsychic dynamics by applying an observational clinical approach. More specifically, we intend to (a) evaluate the representational style of parents informed about the diagnosis of fetal gastroschisis during pregnancy using the Interview of Maternal Representations During Pregnancy and the Interview of Paternal Representations During Pregnancy (M. Ammaniti, C. Candelori, M. Pola, & R. Tambelli, 1995 ) and (b) observe whether the baby's birth influences the parents' representational styles through the application of the same tools (the Interview of Maternal Representations After the Birth, M. Ammaniti & R. Tambelli, 2010, and the Interview of Paternal Representations After the Birth, M. Ammaniti & R. Tambelli, 2010 ), adapted to the postnatal period. During the prenatal period, all parents showed a restricted/disinvested style. Three parents—one mother and two fathers—changed their styles from restricted/disinvested to integrated between pregnancy and Month 6 after the birth of their child. Clinical data from the interviews and observations are discussed in an attempt at better defining intrapsychic dynamics of parents after a diagnosis of gastroschisis.